GEOMORFOLOGICAL ASSESSMENT ON THE ENVIRONMENTAL ANALYSIS OF THE SERRA DAS CONFUSÕES NATIONAL PARK – PIAUÍ STATE – BRAZIL - André Magalhães Rocha; Mônica dos Santos Marçal; Antonio José Teixeira Guerra (Sociedade & Natureza)
The Serra das Confusões National Park is the largest park in northeastern Brazil, with a total area of 502902ha, including 9 municipalities, all in Piauí State, with the headquarters located in Caracol City. The Park is situated on the top of a plateau, latitude 8°30’S; 9°30’S, longitude 43°W; 44°W, drained by channels which flow northwards to Parnaíba river, the main river of Piauí State.Serra das Confusões National Park area is in on morphoestructural and morphoclimatical units inside the Piauí-Maranhão sedimentary basin plateau of the interplateau depression with a semiarid domain, covered by caatinga vegetation (RADAMBRASIL, 1973). The transition zone between Caatinga and Cerrado on the plateau, depressions and complex areas has a vegetation named Carrasco.This paper aims to show a preliminary version regarding geology, geomorphology, pedology and hydrological dynamics on the environmental characterization of the Park and therefore to identify risk areas, to create a use planning and management for the area to improve a better use for these potentials.The Parks geomorphological analysis can be justified by the high importance to understand the natural and social reality of the National Park, showing restrictions on use, always aiming the sustainability of the ecosystem delicate equilibrium, the physical environment, together with the visitor’s safety.